Cancer immunotherapy nursing care from 2004 to 2023: a bibliometric analysis - Li, Linjuan; Ge, Ruyu; Wu, Tingting; Du, Hongyan; Zhang, Xuanwei; Tao, Shiqi; Zhong, Linjun; Li, Mingxia; Fu, Yan; Zhang, Yang (Frontiers in Oncology, 2025)
ObjectiveCancer immunotherapy has become a leading treatment, but research on nursing care specific to this field remains underexplored. This study aims to analyze global trends in cancer immunotherapy nursing care from 2004 to 2023, focusing on key aspects such as patient education, symptom management, immune-related adverse event monitoring, and psychological support.MethodsThe objective of this study was to explore global research trends in cancer immunotherapy nursing care from 2004 to 2023 through bibliometric analysis. A total of 4526 peer-reviewed articles from the Web of Science Core Collection (WoSCC) were selected based on the following criteria: 1) articles related to cancer immunotherapy nursing care, 2) publications written in English, and 3) publications from January 1, 2004 to December 31, 2023. Articles were excluded if they did not meet these criteria or were not directly related to immunotherapy nursing care. The analysis included annual publication trends, country and institution productivity, co-citation analysis, keyword analysis, and burst detection analysis. Tools such as GraphPad, CiteSpace, and VOSviewer were used to visualize the data and identify influential authors, journals, and research topics.ResultsA total of 4526 publications were included. The publication trend showed a consistent annual increase. The United States was identified as the most prolific country, with the University of Texas System being the most productive institution. Cancers published the greatest number of articles in this field. Powles Thomas and Martin Reck were the authors who authored or co-authored the largest number of research papers. The research hotspots included melanoma, non-small cell lung cancer, cytokine release syndrome, and immune-related adverse events. Moving forward, future research could explore enhancing nursing interventions for immune-related side effects and developing standardized care protocols to improve patient outcomes.ConclusionThis study provides valuable insights into the research trends and developments in cancer immunotherapy nursing care over the past two decades. The findings also suggest potential practical applications in clinical nursing practice, particularly in the management of immune-related adverse events and patient education during immunotherapy.